The implementation of Raudhatul Athfal (RA)’s emergency curriculum towards post-covid-19 pandemic: a case study of RA Al-Akhyar in East Cilandak, South Jakarta - Fatimah Azzahro; Hartini Salama (ETUDE: Journal of Educational Research, 2022)
Background: RA encounters the challenge of curriculum adjustment during the Covid-19 pandemic. The RA Emergency Curriculum Guide as a reference requires adjustments to be implemented according to RA’s circumstance.    Purpose: The purpose of this study is to find out the implementation of the Emergency Curriculum at RA Al-Akhyar South Jakarta, in the learning process towards the post Covid-19 pandemic.  Design and methods: This study uses a qualitative approach with research procedures involving observation, interpretation and reporting of research results descriptively. The research subjects are RA Al-Akhyar in South Jakarta and the Principal of RA Al-Akhyar. Research subjects are determined by purposive sampling technique. The research instruments are observation and interviews. Observations are conducted to determine the implementation of the curriculum at RA Al-Akhyar, while interviews are conducted to understand the perspective of the research subjects on curriculum implementation at RA Al-Akhyar.  Results: The results of the study show that during the pandemic, the learning time starts earlier. During the pandemic, the learning method focuses on three (3) methods or their combinations, namely; (1) inquiry learning; (2) project-based learning; and (3) problem-based learning. Utilization of Information Technology and the environment around students is well perceived. During the pandemic, the effectiveness of the material for clean and healthy living behavior, as well as literacy and life skills content is increasing. Meanwhile, the students’ activeness in the learning process is perceived as decreasing